P0727P-CRESYL SULFATE AND INDOXYL SULFATE: A POSSIBLE ROLE AS BIOMARKERS IN THE PREDICTION OF RENAL FUNCTION AND CKD PROGRESSION. (6th June 2020) - Corradi, Valentina; Martino, Francesca; Godi, Llaria; Mattarollo, Cecilia; Barzon, Elena; De Cal, Massimo; Caprara, Carlotta; Giavarina, Davide; Ronco, Claudio
Abstract: Background and Aims: Uremic toxins are markedly accumulated in chronic kidney disease (CKD) patients. Among these two protein-bound compounds, indoxyl sulfate (IXS) and p-cresyl sulfate (PCS) derived from gut bacterial transformation, play an important role. Recent evidences demonstrate their toxic effects in vitro and may contribute in vivo to CKD progression and mortality in uremic patients. For this reason, bacterial metabolism and its metabolites are therapeutic targets in CKD. While, several studies have evaluated possible associations between these two compounds and renal function decline in CKD, while no study has evaluated them according to the stage of progression (CKD stage). In this study, PCS and IXS are considered to highlight the possible role as biomarkers in the prediction of renal function and CKD progression (GFR stage 1-5). Method: In our observational, prospective study we evaluated total (t) and free (f) PCS and IXS plasmatic fractions using Ultra High Performance Liquid Chromatography Infinity 1260 (Agilent technologies) coupled to an API 3200™ triple quadrupole mass spectrometry (ABSciex). Data were shown as mean ± SD or median (25 th -75 th ). Statistical analysis was done by SPSS version 24.0 Results: We evaluated 80 CKD patients: 54.68 ± 12.88 yrs, 39 F and 41 M. The median creatinine was 1.58 (0.90-3.32) mg/dL, median urea 58.50 (42.0-121.25) mg/dL and eGFR (CKD-EPI) 42 (17.25-85.75) mL/min/1.73 m 2 . On the table 1, it was summarized the levels of PCS and IXS in all patients and classified by GFR (G) stages. We found the statistically significant increase of total and free fractions of PCS ( p <0.001) and IXS ( p <0.001) with the progression of CKD by G stage and inverse strong correlation between eGFR (CKD-EPI) and PCSt ( Spearman's Rho (r)=-0.70, p <0.001), PCSf (r=-0.75, p <0.001), IXSt (r=-0.76, p <0.001), IXSf (r=-0.82, p <0.001). Moreover, the increase of PCS and IXS predicts the eGFR decline significantly, according to the linear regression model using eGFR as dependent variable: PCSt (R-squared (R 2 )= 0.34, p <0.001). PCSf (R 2 =0.21, p <0.001). IXSt (R 2 =0.27, p <0.001). IXSf (R 2 =0.19, p <0.001). By multivariate analysis, the total compounds of both toxins remain predictive of eGFR: PCSt (β=-0.72, p =0.003; 95%CI:-2.43;-0.54) and IXSt (β=-0.70, p =0.011; 95%CI:-5.15;-0.70). Conclusion: In conclusion, in our study we show the strong correlations between and PCS and IXS and eGFR and we found the significantly increase of PCS and IXS (total and free) with the progression of CKD in all G stage (1-5). We highlight the use of mass spectrometry in the evaluation of renal function especially in the earliest stages of CKD with the possibility of measuring minimum concentrations of PCSf and IXSf. Assuming the predictive value of PCS and IXS towards the reduction of eGFR, we could hypothesize the identification of cut-offs based on confidence intervals, for the prediction and progression of renal function impairment.